RESISTANT DYSPHEMISM IN MIN AJLI HUWIYYAH’S POETRY BY AHLAM MOSTEGHANEMI: DISFEMISME RESISTEN DALAM PUISI MIN AJLI HUWIYYAH KARYA AHLAM MOSTEGHANEMI - Dzikrul Hakim Tafuzi Mu'iz; Elisa Nurul Laili (Program Studi Bahasa dan Sastra Arab STIABI Riyadul 'Ulum, 2024)
Ahlam Mosteghanemi uses dysphemism in the poem Min Ajli Huwiyyah to describe the identity crisis of Algerian Arabs influenced by French culture since the 1970s. This study aims to examine dysphemism as a form of inferiority of Arab identity represented by the Algerian nation towards France. The data were obtained using the documentation technique of Min Ajli Huwiyyah's poem and then analysed using the content analysis technique to interpret the data based on Allan-Burridge's dysphemism. The research findings show that literary works become a medium of resistance to disseminate resistance by presenting dysphemism through taboo terms, curses, physical epithets, racist expressions, and disrespectful mockery. In detail, the five indicators of dysphemism are found in these literary works that supported social criticism at that time. This study concludes that Min Ajli Huwiyyah reflects Algerian cultural resistance to French domination through dysphemistic expressions. The study recommends a more recent comparative analysis of literary works to understand the dynamics of modern Arab identity, especially in Algeria, which continues to evolve with the changing times.